High serum caspase-3 levels in hepatocellular carcinoma prior to liver transplantation and high mortality risk during the first year after liver transplantation. (3rd July 2019) - Lorente, Leonardo; Rodriguez, Sergio T.; Sanz, Pablo; González-Rivero, Agustín F.; Pérez-Cejas, Antonia; Padilla, Javier; Díaz, Dácil; González, Antonio; Martín, María M.; Jiménez, Alejandro; Cerro, Purificación; Portero, Julián; et al.
ABSTRACT: Background : Higher liver caspase-3 activity has been found in patients with different liver diseases. However, there is no published data about circulating caspase-3 levels in patients with hepatocellular carcinoma (HCC) who underwent liver transplantation (LT). Therefore, our objective in this study was to determine whether an association between circulating caspase-3 levels in HCC patients prior to LT and one-year mortality after LT exists. Methods : In this observational and retrospective study, we included HCC patients who underwent LT. We measured serum levels of caspase-3 (as the main executor of apoptosis) and caspase-cleaved cytokeratin (CCCK)-18 (to estimate apoptosis degree) before LT. Results : One-year surviving LT patients (n = 129) showed lower serum levels of caspase-3 (p = 0.004) and CCCK-18 (p = 0.001) than non-surviving LT patients (n = 16). Logistic regression analysis showed that serum caspase-3 levels prior to LT were associated with one-year after LT mortality (Odds Ratio = 2.612; 95% CI = 1.519–4.493; p = 0.001). We found a positive association between serum levels of caspase-3 and CCCK-18 (rho = 0.26; p = 0.002). Conclusions : Our study is the first one reporting data of circulating caspase-3 levels prior to LT for HCC, and an association between high serum caspase-3 levels previously to LT and survival at first year after LT.